2007
DOI: 10.1614/wt-06-050.1
|View full text |Cite
|
Sign up to set email alerts
|

Dry Bean Response to Preemergence-Applied KIH-485

Abstract: Three field trials were conducted over a 2-yr period (2004 and 2005) at Exeter and Ridgetown, Ontario to evaluate the tolerance of eight market classes of dry beans to KIH-485 applied PRE at 210 and 420 g ai/ha. KIH-485 PRE caused as much as 67% visual injury in small-seeded and 44% visual injury in large-seeded dry beans. KIH-485 applied PRE at 420 g/ha reduced plant height up to 47% at Ridgetown and 8% at Exeter in 2004, and reduced height of brown and white bean by 15 and 19%, respectively, but had no effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
12
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 12 publications
6
12
0
Order By: Relevance
“…In other studies, linuron applied PRE at various doses did not cause any adverse affect on the yield of cranberry, kidney, and white beans but yield of black bean was reduced 16% compared to the nontreated control at 2500 g·ha −1 [16]. These results are similar to other studies in which flumioxazin, pyroxasulfone, and alachlor applied preemergence which caused no losses in cranberry and kidney bean seed yield [6,25,26].…”
Section: Seed Moisture Content and Yieldsupporting
confidence: 84%
“…In other studies, linuron applied PRE at various doses did not cause any adverse affect on the yield of cranberry, kidney, and white beans but yield of black bean was reduced 16% compared to the nontreated control at 2500 g·ha −1 [16]. These results are similar to other studies in which flumioxazin, pyroxasulfone, and alachlor applied preemergence which caused no losses in cranberry and kidney bean seed yield [6,25,26].…”
Section: Seed Moisture Content and Yieldsupporting
confidence: 84%
“…When compared to AP-3, Georgia Green is considered to be a small-seeded peanut cultivar (Branch 1996;Gorbett 2007). Previous research concluded that smaller-seeded market classes of dry bean were more sensitive to PRE applications of pyroxasulfone than dry beans with larger seeds (Sikkema et al 2007). In soybean, it has been speculated that plants developing from larger seeds could survive lethal herbicide doses better than plants developing from smaller seeds because they could survive on more cotyledonary food reserves until the herbicide dosage reaches a non-lethal level (Anderson 1970).…”
Section: Resultsmentioning
confidence: 99%
“…In other legume crops, PPI or PRE applications of pyroxasulfone at rates $ 209 g ai/ha caused significant yield reductions (Soltani et al 2008;Sikkema et al 2007). While there was significant crop injury (stunting) from pyroxasulfone applied PRE at Plains, there was no correlation between this injury and peanut yield for application timing at either location (Figure 3).…”
Section: Yieldmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research indicated decreased pyroxasulfone injury with legumes grown in soils with greater clay contents [19]. Canadian dry bean research indicated that pyroxasulfone injury at 210 g/ha was 11% or less [55]. These data indicate that at rates up to 160 g ha −1 wheat had tolerance in sandy loam, loamy sand, and sandy clay loam soils of the Southeastern United States.…”
Section: Crop Response and Weed Controlmentioning
confidence: 72%